Britain in brief - London. Foreign and Commonwealth Office (London The Foreign and Commonwealth Office, 1997)
This CD-ROM is an "Interactive high tech voyage through the British Isles" It contains colorful images and 30 "information zones" of England, Scotland, Northern Ireland and Wales. The welfare, health, beliefs, religions, diet, education climate, wildlife conservation, land use and farming, pollution control, leisure past times, sports and exercise, monarchy, local government, law, armed forces, Britain and the world, money and finance, transport, communications, industry, science and technology.
Keywords: Great Britain -- History; Great Britain -- Civilization; Great Britain -- Economic conditions; Great Britain -- Social conditions; Great Britain -- Politics and government